2012
DOI: 10.1155/2012/742829
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Cellular Distribution of INHA and INHB before and afterIn VitroCultivation of Porcine Oocytes Isolated from Follicles of Different Size

Abstract: Cumulus-oocyte-complexes (COCs) were collected from small (<3 mm), medium (3–5 mm), and large (>5 mm) porcine follicles, and the INHA and INHB expression and cellular localization were studied. Developmentally competent (BCB+) COCs were cultured for 44 h. Samples of mRNA were isolated before and after in vitro maturation (IVM) from oocytes collected from follicles of different size for RQ-PCR assay. The INHA and INHB protein distribution within the oocytes was observed by confocal microscopy. INHA mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In relation to the INHBA gene, previous studies have demonstrated a higher expression in porcine MF‐derived oocytes, than in those derived from SF after IVM (Kempisty et al., 2012) and in protein prior to and after IVM (Kempisty et al., 2015); similar findings were described in the case of MII bovine oocytes compared with GV oocytes (Leal et al, 2011). Our results point to INHBA expression being similar in CCs.…”
Section: Discussionsupporting
confidence: 54%
“…In relation to the INHBA gene, previous studies have demonstrated a higher expression in porcine MF‐derived oocytes, than in those derived from SF after IVM (Kempisty et al., 2012) and in protein prior to and after IVM (Kempisty et al., 2015); similar findings were described in the case of MII bovine oocytes compared with GV oocytes (Leal et al, 2011). Our results point to INHBA expression being similar in CCs.…”
Section: Discussionsupporting
confidence: 54%
“…The average FPKM of the INHA gene in the ovary is 371, which is distributed in the peripheral region of the cytoplasm in the oocytes of large follicles and exists in the whole cytoplasm in the oocytes of small follicles; after in vitro fertilization, INHA is strongly expressed in the oocytes of small follicles, especially in the zona pellucida. Before and after in vitro fertilization, the INHB protein is highly expressed in the oocytes and cytoplasm of small follicles, and INHs can be used as a marker of porcine oocyte quality [27]. INHBA was involved in the synthesis of inhibin A/AB.…”
Section: Discussionmentioning
confidence: 99%
“…The next gene that showed a decrease in expression after IVM is inhibit subunit beta A (INHBA). It is believed that it plays an important role in reproduction and development through the coding of activins from TGF-beta superfamily [ 84 , 85 ] and is involved in the secretion of FSH from the pituitary [ 86 ], being also a marker of porcine oocyte quality [ 87 ]. A study on boars showed that INHBA is significant in testicular development, especially during puberty [ 88 ].…”
Section: Discussionmentioning
confidence: 99%